Late time cosmology in f(R, G)-gravity with interacting fluids. (1st March 2022) - Paul, B C; Chanda, A; Beesham, A; Maharaj, S D
Abstract: Cosmological models are obtained in a f ( R ) modified gravity with a coupled Gauss–Bonnet (GB) terms in the gravitational action. The dynamical role of the GB terms is explored with a coupled dilaton field in two different cases (I) f ( R ) = R + γ R 2 − λ R 3 m s 2 δ where γ, λ and δ are arbitrary constants and (II) f ( R ) = R and estimate the constraints on the model parameters. In the first case we choose GB terms coupled with a free scalar field in the presence of interacting fluid and in the second case GB terms coupled with scalar field in a self interacting potential to compare the observed Universe. The evolutionary scenario of the Universe is obtained adopting a numerical technique as the field equations are highly non-linear. Defining a new density parameter Ω H, a ratio of the dark energy (DE) density to the present energy density of the non-relativistic matter, we look for a late accelerating Universe. The state finder parameters Ω H, deceleration parameter ( q ), jerk parameter ( j ) are plotted. It is noted that a non-singular Universe with oscillating cosmological parameters for a given strength of interactions is admitted in model-I. The gravitational coupling constant λ is playing an important role. The Lagrangian density of f ( R ) is found to dominate over the GB terms when oscillating phase of DE arises. In model-II, we do not find oscillation of the cosmological parameters as the Universe evolves. In the presence of interaction the energy from radiation sector of matter cannot flow to the other two sectors of fluid. The range of values of the strengths of interaction of the fluids are estimated for a stable Universe assuming the primordial gravitational wave speed equal to unity.